History in the United States, 1800-1860 Its Practice and Purpose - Callcott, George H. (Johns Hopkins University Press, 2019)
Originally published in 1970. Professor Callcott's analysis of the rise of historical consciousness in the United States from 1800 to 1860 offers a new dimension to American historiography. Other books have provided insight into the works of Bancroft, Parkman, and others, but Callcott goes beyond to explain the meaning of the past itself rather than the contributions of particular historians. As the anatomy of an idea, this is an important contribution to American intellectual history; and as a study of humans' need for the past and their use of it, it is an important contribution to American social history. The author begins by analyzing the European and Romantic background for American historical thought. He then explores the rise of historical themes in literature, education, the arts, and scholarship. By describing the type of historical subject matter, the methods of writing history, the interpretive themes historians used, and the standards by which critics judged history, Callcott offers a new understanding of the social and personal meaning that history had for Americans at the time. The American people were especially convinced of the utility of history-its social use in supporting accepted values, its personal utility in extending human experience, and its philosophical value in pointing people toward ultimate reality. The idea of history possessed a remarkable coherence that reflected the preoccupations and aspirations of the young nation. Callcott also demonstrates, however, that when basic historical assumptions were challenged by controversy, the entire edifice collapsed.